Evaluation of corrosion product formed on carbon steel in recycled sour water of overhead system - Ismail, Azzura; Mahari, Syamimi; Shamsuddin, Firdaus; Hasan, Norhariti; Ramli, Nursyazwani (International Journal of Integrated Engineering, 2019)
Corrosion rate of carbon steel in recycled sour water, dilution sour water and 3.5%NaCl was investigated by electrochemical test and immersion. The results revealed as the corrosion product developed on carbon steel, the corrosion rate was linearly decreased in both solutions. The sour water properties were investigated using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) to detect metal elements. The properties of corrosion product have been characterized using Scanning Electron Microscopy (SEM) and while the mechanical properties of carbon steel were identified using hardness test. SEM reveals corrosion products of patch pattern with some spiky flower. Corrosion properties of carbon steel in sour and seawater was performed using Electrochemical testing with Tafel plot while weight loss was identified by immersion test. It was observed that as immersion time increased, corrosion rate decreased due to passivation effect by corrosion product.